Control of vessel diameters mediated by flow-induced outward vascular remodeling in vitro. (7th July 2020) - Sano, Hiromu; Watanabe, Masafumi; Yamashita, Tadahiro; Tanishita, Kazuo; Sudo, Ryo
Abstract: Vascular networks consist of hierarchical structures of various diameters and are necessary for efficient blood distribution. Recent advances in vascular tissue engineering and bioprinting have allowed us to construct large vessels, such as arteries, small vessels, such as capillaries and microvessels, and intermediate-scale vessels, such as arterioles, individually. However, little is known about the control of vessel diameters between small vessels and intermediate-scale vessels. Here, we focus on vascular remodeling, which creates lasting structural changes in the vessel wall in response to hemodynamic stimuli, to regulate vessel diameters in vitro . The purpose of this study is to control the vessel diameter at an intermediate scale by inducing outward remodeling of microvessels in vitro . Human umbilical vein endothelial cells and mesenchymal stem cells were cocultured in a microfluidic device to construct microvessels, which were then perfused with a culture medium to induce outward vascular remodeling. We successfully constructed vessels with diameters of 40–150 μ m in perfusion culture, whereas vessels with diameters of <20 μ m were maintained in static culture. We also revealed that the in vitro vascular remodeling was mediated by NO pathways and MMP-9. These findings provide insight into the regulation of diameters of tissue-engineered blood vessels. This is an important step toward the construction of hierarchical vascular networks within biofabricated three-dimensional systems.